2015
DOI: 10.1002/pbc.25662
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Cohort Study of Inferior Vena Cava Filter Use in Children

Abstract: IVC filter placement in pediatric patients remains a rare event and is most common in adolescents. Unlike in adults, pediatric IVC filter placement does not appear to be increasing over time and is predominantly used in the setting of a venous thrombotic event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
0
18
2
Order By: Relevance
“…Data reliability and quality are assured through a joint effort between the participating hospitals and the Children's Hospital Association. 19,20 Data are deidentified at the time of submission and subject to a number of validity and reliability checks before being included in the dataset. For the purpose of this study, data from all 48 participating hospitals were included.…”
Section: Data Sourcementioning
confidence: 99%
“…Data reliability and quality are assured through a joint effort between the participating hospitals and the Children's Hospital Association. 19,20 Data are deidentified at the time of submission and subject to a number of validity and reliability checks before being included in the dataset. For the purpose of this study, data from all 48 participating hospitals were included.…”
Section: Data Sourcementioning
confidence: 99%
“…In addition, the Society of Interventional Radiology supports the prophylactic use IVC filters in certain high-risk situations, such as severe trauma. 95 A recent multicenter study on the use of IVC filters in children across tertiary care centers in the United States found that the placement of filters remains a relatively uncommon intervention in pediatric VTE (mean yearly incidence of 6 per 100,000 admissions). 95 This study found that, unlike adult patients in whom the majority of filters are placed for prophylactic indications (i.e., after severe trauma, malignancy, or orthopedic surgery), only a small proportion of IVC filters ($24%) are placed prophylactically in children.…”
Section: Mechanical Approaches In Vte Inferior Vena Cava Filtersmentioning
confidence: 99%
“…95 A recent multicenter study on the use of IVC filters in children across tertiary care centers in the United States found that the placement of filters remains a relatively uncommon intervention in pediatric VTE (mean yearly incidence of 6 per 100,000 admissions). 95 This study found that, unlike adult patients in whom the majority of filters are placed for prophylactic indications (i.e., after severe trauma, malignancy, or orthopedic surgery), only a small proportion of IVC filters ($24%) are placed prophylactically in children. The majority of IVC filters in the pediatric population were used in adolescent patients with either a lower extremity DVT or PE and contraindications for anticoagulation.…”
Section: Mechanical Approaches In Vte Inferior Vena Cava Filtersmentioning
confidence: 99%
See 2 more Smart Citations